Skill Moderators of the Effects of a Reading Comprehension Intervention. (January 2019) - Clemens, Nathan H.; Oslund, Eric; Kwok, Oi-man; Fogarty, Melissa; Simmons, Deborah; Davis, John L.
This study utilized secondary analyses of a randomized controlled trial and investigated the extent to which prestest word identification efficiency, reading fluency, and vocabulary knowledge moderated the effects of an intervention on reading comprehension outcomes for struggling readers in sixth through eighth grades. Given that the experimental intervention included components that targeted word reading, reading fluency, and vocabulary, we hypothesized that students with lower pretest performance in those skill domains would benefit more from the intervention compared to students with relatively stronger pretest performance or students who received school-implemented (business-as-usual) intervention. Results indicated that pretest word identification efficiency and vocabulary did not moderate the effects of the intervention; however, moderation effects were observed for pretest oral reading fluency such that reading comprehension gains of students with lower pretest fluency were greater in the experimental intervention compared to students with higher pretest fluency or in the comparison condition. Reasons for the moderation effect are discussed. Findings underscore the use of moderation analyses when evaluating multicomponent interventions.